Being reformed: Subjectification and security sector reform in the Congolese armed forces. Issue 2 (3rd April 2017) - Baaz, Maria Eriksson; Stern, Maria
ABSTRACT: In contrast to most studies addressing security sector reform (SSR) in Africa, this article queries defence reform efforts in the Democratic Republic of the Congo (DRC) from a governmentality perspective and hones in on processes of subjectification and modes of agency among members of the Armed Forces of the DRC (FARDC). Based on extensive field research in the DRC, it explores how army staff produce themselves through (and outside of) the ways in which they are 'hailed' into subject positions in donors' efforts to govern. In asking how FARDC staff respond, position, and produce themselves in relation to external reform efforts and the attending governing technologies and techniques, the article contributes to the increasing – yet limited – scholarly attention to those being 'reformed' through SSR efforts. Ultimately, attending to the specificities of how processes of subjectification are experienced from the perspective of those who are to be reformed problematizes the simplified notions of lack of political will and commitment, obstruction and 'spoilers' that are so prevalent in the SSR literature, suggesting that these processes are heavily shaped by memories of colonialism and exploitation.